MARKETING PRICING IN A FREE MARKET - CHEREP, OLEKSANDR; KOTSERUBA, А. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The problems related to shaping a  company's pricing policy are the object of research conducted by the scholars in the fields of economics, management, marketing, entrepreneurship, finance, and accounting. This determines the multivariance of the approaches to interpreting the concept of "pricing policy", determining the main stages of shaping the pricing policy and their content. The place of the marketing pricing policy in the company's development policy and its relationship with other policies are established. The types of the  company's pricing policy are defined. In the process of systematizing the recognised interpretations, the scholars identified the following main theoretical approaches to the interpretation of the concept of "marketing pricing policy". When addressing the issue of shaping a pricing policy, any company should determine the level of intensity of using the price as a strategic marketing tool. It is suggested to divide companies into groups depending on this criterion. The dependence of the  company's  marketing pricing policy on the strategy of its behavior in the market is established. The types of the marketing pricing policy are proposed.
Keywords: Pricing policy; pricing; marketing pricing policy; forms; types; price; strategies; consumer; active and passive pricing; goals